Cas9-specific immune responses compromise local and systemic AAV CRISPR therapy in multiple dystrophic canine models - Hakim, Chady H.; Kumar, Sandeep R. P.; Pérez-López, Dennis O.; Wasala, Nalinda B.; Zhang, Dong; Yue, Yongping; Teixeira, James; Pan, Xiufang; Zhang, Keqing; Million, Emily D.; Nelson, Christopher E.; Metzger, Samantha; et al. (Nature Communications, 2021)
Adeno-associated virus (AAV)-mediated CRISPR-Cas9 editing holds promise to treat many diseases. The immune response to bacterial-derived Cas9 has been speculated as a hurdle for AAV-CRISPR therapy. However, immunological consequences of AAV-mediated Cas9 expression have thus far not been thoroughly investigated in large mammals. We evaluate Cas9-specific immune responses in canine models of Duchenne muscular dystrophy (DMD) following intramuscular and intravenous AAV-CRISPR therapy. Treatment results initially in robust dystrophin restoration in affected dogs but also induces muscle inflammation, and Cas9-specific humoral and cytotoxic T-lymphocyte (CTL) responses that are not prevented by the muscle-specific promoter and transient prednisolone immune suppression. In normal dogs, AAV-mediated Cas9 expression induces similar, though milder, immune responses. In contrast, other therapeutic (micro-dystrophin and SERCA2a) and reporter (alkaline phosphatase, AP) vectors result in persistent expression without inducing muscle inflammation. Our results suggest Cas9 immunity may represent a critical barrier for AAV-CRISPR therapy in large mammals.
Gesehen am 27.01.2022